Synthesis and Optical Properties of Triphenylene-Based Donor-Donor and Donor-Acceptor Conjugated Polymers: A Comparative Study - Yong Li; Dung D. Nguyen; Kuldeep Shetye; Zhonghua Peng (International Journal of Polymer Science)
Two new conjugated polymers (P1 and P2), containing a bithiophene donor unit coupled with either a triphenylene donor unit or an imide-functionalized triphenylene acceptor unit in the backbone, have been synthesized, structurally characterized, and comparatively studied by using 1H NMR, FT-IR, gel permeation chromatography, differential scanning calorimetry, cyclic voltammetry, ultraviolet-visible absorption, and fluorescence spectroscopy. Both polymers are amorphous in nature and thermally stable up to 450°C. The inclusion of the imide functionalization in the triphenylene unit significantly lowered the lowest unoccupied molecular orbital energy level and thus the bandgap of the donor-acceptor polymer P2 over the donor-donor polymer P1. P1 and P2 show very different optical properties in hexane and other solvents. P1 shows a broad emission in hexane but vibronically structured emissions in other solvents; in contrast, P2 exhibits a vibronically resolved emission in hexane, while exhibiting redshifted, broad, and featureless emissions in other solvents. P1 takes a random coil conformation in good solvents like p-xylene, benzene, toluene, anisole, chloroform, THF, and o-dichlorobenzene, whereas in hexane, it may adopt a helical folding conformation. In the poor solvent DMSO, interchain aggregates dominate. P2, on the other hand, adopts a random coil conformation in hexane but possibly the helical folding conformation in other good solvents. The opposite conformations of the two polymers may be responsible for their opposite solvent-dependent fluorescence properties. By virtue of the very different fluorescence properties of these two polymers in nonpolar solvents such as hexane and in polar solvents, the potential of using the polymers to detect the trace amount of ethanol content that is added to gasoline has been revealed with high sensitivity.